2000
DOI: 10.4049/jimmunol.164.9.4868
|View full text |Cite
|
Sign up to set email alerts
|

Ley/H: An Endothelial-Selective, Cytokine-Inducible, Angiogenic Mediator

Abstract: Endothelial cells (ECs) are key participants in angiogenic processes that characterize tumor growth, wound repair, and inflammatory diseases, such as human rheumatoid arthritis (RA). We and others have shown that EC molecules, such as soluble E-selectin, mediate angiogenesis. Here we describe an EC molecule, Lewisy-6/H-5-2 glycoconjugate (Ley/H), that shares some structural features with the soluble E-selectin ligand, sialyl Lewisx (sialyl Lex). One of the main previously recognized functions of Lewisy is as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…Similar aberrant expression of blood group type 2 antigens, Le y /H, in vascular endothelial cells in inflammatory disease was reported, in which Le y /H antigen expression was rapidly induced by immune modulators, cytokines, lipopolysaccharide, phorbol-12-myristate-13-acetate, calcium ionophore, thrombin, histamine, and growth factors (Koch et al 1994;Halloran et al 2000). Enhanced expression of Le y /H antigens was observed in diseased skin tissues such as psoriatic skin, which was quite similar to the A type 3 antigen expression pattern.…”
Section: Discussionsupporting
confidence: 59%
“…Similar aberrant expression of blood group type 2 antigens, Le y /H, in vascular endothelial cells in inflammatory disease was reported, in which Le y /H antigen expression was rapidly induced by immune modulators, cytokines, lipopolysaccharide, phorbol-12-myristate-13-acetate, calcium ionophore, thrombin, histamine, and growth factors (Koch et al 1994;Halloran et al 2000). Enhanced expression of Le y /H antigens was observed in diseased skin tissues such as psoriatic skin, which was quite similar to the A type 3 antigen expression pattern.…”
Section: Discussionsupporting
confidence: 59%
“…In another in vivo investigation, increased Le y expression has been found on vascular endothelium from patients with rheumatoid arthritis where Le y was cytokine inducible. 20 These results certainly identify the significance of Le y in vascular inflammation. It is more interesting to notice that the result of tissue Western blot showed several increasing bands in vessels after ligation ( Figure 6A), indicating that there are some specific molecules carrying Le y that are induced in the injured vasculature and probably involve in leukocyte adhesion.…”
mentioning
confidence: 81%
“…13,17,18 Meanwhile, recent studies have demonstrated that Le y is upregulated in synovial endothelium and joint fluid in rheumatoid arthritis. 19,20 Le y is also found to be expressed on intercellular adhesion molecule-2 (ICAM-2) on endothelial cells. ICAM-2 is a ligand of dendritic cell-specific C-type lectin, dendritic cell-specific ICAM-3-grabbing nonintegrin.…”
mentioning
confidence: 99%
“…Hypervascularity and hypercoagulability are typical characteristics of RCC and play significant roles in tumor proliferation and metastasis [22]. In the non-O blood group, deletion of A or B antigens induces up-regulation of precursor H and Lewis y expression, and both precursors exert angiogenic effects [23]. Also, the ABO group is a major determinant of plasma levels of von Willebrand factor (vWF) and factor VIII [24], which are detected in the endothelial cells of RCC [25].…”
Section: Discussionmentioning
confidence: 99%